Donors' Satisfaction with Egg Donation and Willingness to Re-donation: A Systematic Review Article - Hanie Balochi; Fatemeh Hadizadeh Talasaz; Narjes Bahri (Mashhad University of Medical Sciences, 2020)
Introduction: Demand for egg donors is growing worldwide. Due to the acute shortage of egg donors worldwide and since donors' satisfaction affect their willingness to re-donate, therefore, this study was conducted with aim of a systematic review of studies on donors' satisfaction with egg donation and willingness to re-donate in Iran and the world. Methods: Comprehensive searches were performed in databases of Magiran, SID, Irandoc, Scopus, Pubmed, ISI as well as Google Scholar search engine from 1990 to 2020. To search the studies, Persian and English keywords including: egg, ovum, oocyte, satisfaction, donor, Re-donation and combining these words with AND and OR operators were used. According to STROBE criteria, the studies which scored above 15 were included in the study. Data analysis was performed qualitatively. Results: Out of 63 articles found in the databases, 7 articles which met the inclusion criteria were reviewed. All of these articles were of good or average quality.The results of the studies showed that egg donors evaluated the donation experience positively, so that the level of satisfaction was high and many of them were willing to donate eggs again. Conclusion: Despite the high satisfaction of donors, determining and implementing the methods to improve donor satisfaction leads to better selection and retention of donors.